TEHNIK KALKULUS DERIVATIF UNTUK FUNGSI PERMINTAAN TENAGA KERJA HICKSIAN DAN MARSHALLIAN - Sidik Budiono (Jurnal MEDIAN Arsitektur dan Planologi, 2011)
This paper explain how demand for labor derived from firm activities. The methods used in this study are calculus of derivation. Author use this methods to explore firms activity in economic principals. The firm choose one of economic principals on cost minimization or profit maximization. Based on theoretical study it implies that Solow Elasticity Function is the Hicksian Demand Function for labour factor. it is different from Phelps (2006) as Solow Elasticity is result of demand for labor and supply of labor. We also can explain here that the real wage has negative correlation with employment as different from Phelps’s conclusion that is positive. The next study is done by performing a derivation toward the company’s profit function and it results in the Marshallian demand function for the production factor (labour). So it can be concluded that the real wage has negative correlation with employment in the labour demand function.